Hematological indices - a possible marker of subclinical inflammation in very elderly patients and centenarians - Nataliya V. Bagisheva; Tatyana A. Eliseeva; Olga I. Turna; Olga N. Vakulenko; Leonid I. Bubman; Margarita A. Romanova; Karine A. Lytkina; Georgiy G. Melkonyan; Svetlana A. Rachina; Leonid I. Dvoretsky (LLC "MEDIAFORMAT", 2024)
Aim. To study the possibility of using hematological indices as markers of subclinical inflammation in very elderly patients and centenarians with coronary artery disease (CAD). Materials and Methods: The cross-sectional study enrolled 127 patients; 93 patients with CAD - in the study group, 34 patients without CAD - in the control group. The mean age of patients reached 88.2±5.3 years (76-98 years); 48.8% were over 90 years of age. The ratio of the number of neutrophils to lymphocytes (NLR), neutrophils to monocytes (NMR), platelets to lymphocytes (PLR), lymphocytes to monocytes (LMR) and the systemic immune-inflammation index (SII) were determined. Interleukin-6 (IL-6) was determined in all patients, tumor necrosis factor (TNF)-α - in 49 patients. Results. In patients with coronary artery disease, the mean content of leukocytes was significantly higher than in the control group (6.1±1.5 and 5.4±1.5×109/l, respectively, p=0.02), and platelets were less (212±60 and 243±78×109/l, respectively, p=0.02). The platelet-lymphocyte ratio (139±54 and 185±87, p=0.001), neutrophils-monocytes ratio (12.4±13.4 and 20.8±22.0; р=0.04) and systemic immune-inflammatory index (554±345 and 762±616; p=0.02) were lower in patients with CAD. In patients with heart failure, a significantly higher content of leukocytes was revealed (6.5±1.7 and 5.7±1.4×109/l, respectively, p=0.009). A direct correlation was established between NLR and the concentration of IL-6 (r=0.26; p=0.003), as well as an inverse correlation with the content of TNF-α (r=-0.3; p=0.03). Inverse correlation was registered between the NLR and functional abilities of patients (for Barthel index: r=-0.35; p<0.0001; for IADL scale: r=-0.34; p<0.0001). There was a direct correlation between NLR and the risk of falls by the Morse scale (r=0.38; p=0.001). Direct relationships between TLR and IL-6 (r=0.18; p=0.04), ESR (r=0.20; p=0.02) and the values of the Morse Fall Scale (r=0.43; p<0.0001) were observed. An inverse correlation was registered between TLR and TNF-α (r=-0.43; p=0.002), Barthel index (r=-0.20; p=0.02), IADL scale (r=-0.21; p=0.01) and bone mineral density in the femur (r=-0.2; p=0.03). A direct correlation of systemic immune-inflammation index with IL-6 (r=0.24; p=0.006) and the values of the Morse Fall Scale (r=0.49; p<0.0001), as well as an inverse relationship with TNF-α (r=-0.36; p=0.01), Barthel index (r=-0.26; p=0.02) and IADL scale (r=-0.3; p=0.001) were observed. Conclusion. Various hematological indices can be used as markers of subclinical inflammation in patients with coronary artery disease in old age and in centenarians.